2012
DOI: 10.1371/journal.pone.0043142
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonate 15-Lipoxygenase Type B Knockdown Leads to Reduced Lipid Accumulation and Inflammation in Atherosclerosis

Abstract: Inflammation in the vascular wall is important for development of atherosclerosis. We have shown previously that arachidonate 15-lipoxygenase type B (ALOX15B) is more highly expressed in human atherosclerotic lesions than in healthy arteries. This enzyme oxidizes fatty acids to substances that promote local inflammation and is expressed in lipid-loaded macrophages (foam cells) present in the atherosclerotic lesions. Here, we investigated the role of ALOX15B in foam cell formation in human primary macrophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
0
46
0
1
Order By: Relevance
“…In addition, 15-LOX-2 is expressed in macrophages (7,34,35), and expression is regulated by hypoxia-inducible factor-1␣ (35). Moreover, knockdown of 15-LOX-2 expression in human primary macrophages and in mice (in this case, the target was 8-LOX, the murine homologue of 15-LOX-2) decreased lipid accumulation and inflammation, hallmarks of atherosclerosis (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 15-LOX-2 is expressed in macrophages (7,34,35), and expression is regulated by hypoxia-inducible factor-1␣ (35). Moreover, knockdown of 15-LOX-2 expression in human primary macrophages and in mice (in this case, the target was 8-LOX, the murine homologue of 15-LOX-2) decreased lipid accumulation and inflammation, hallmarks of atherosclerosis (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, silencing expression of murine ALOX15B (which produces 8-HPETE from AA rather than 15-HPETE) mitigated plaque formation (8). These studies appear to be at odds: the former indicates that it is the product of a 15-LOX that promotes plaque formation, whereas one might infer from the latter studies that 8-HETE should be the proinflammatory lipid mediator in the mouse model.…”
Section: -Lox-2 and 5-lox Differ In The Orientations Of Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support our suggestion that m8S-LOX may generate 15-HETE in a cellular context, because these knock-out mice generate 15-HETE in the absence of the 15-LOX-1 counterpart (ϳ40% sequence identity with 15-LOX-2). Moreover, Magnusson et al (6) have demonstrated that ALOX15B gene-silencing experiments in human primary macrophages decrease cellular lipid accumulation and that the equivalent knockdown in a murine model (LDLR Ϫ/Ϫ ) leads to a reduction in markers of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, 4 overlapped genes (A LOX15B, CCL11, NLRP2 and SERPINA3) were identified in IIA vs. IB and IIA vs. IIB. The knockdown of the human arachidonate 15-lipoxygenase type B (ALOX15B) was reported to reduce the inflammation and lipid accumulation, suggesting its active pro-inflammatory and proatherogenic role (20). Pyrin domain-containing protein 2 (NALP2) was characterized by an N-terminal pyrin domain (PYD).…”
Section: Discussionmentioning
confidence: 99%